ATTEMPT TO MEASURE AND ASSESS THE IMPACT OF GROWTH IN EL-KALA CITY USING GEOGRAPHICAL INFORMATION SYSTEMS - Keblouti Sarra; Bousmaha Ahmed (International Journal of Innovative Technologies in Social Science, 2025)
This study aims to assess the urban growth dynamics of the city of El-Kala between 2008 and 2024, adopting a diachronic approach using geographic information systems (GIS) and remote sensing. The aim is to quantify and spatialize the city's expansion over this period, and identify its main causes.Satellite images of the years between 2008 and 2024 will be processed using GIS to map land use at these different dates. Diachronic analysis will enable us to measure urban growth in terms of built-up areas gained between each date.The results will make it possible to assess the sprawl dynamics of the city of El-Kala over the 2008-2024 period, both quantitatively and spatially. The main drivers of this expansion can be identified.